Design of Silica Multimode Optical Fibers with Extremely Enlarged Core Diameter for Laser-Based Multi-Gigabit Short-Range Optical Networks - Anton V. Bourdine; Vladimir A. Burdin; Vijay Janyani; Ashish Kumar Ghunawat; Ghanshyam Singh; Alexander E. Zhukov (Photonics, 2018)
This work presents an alternative fast and simple method for the design of a refractive index profile of silica multimode optical fibers (MMFs) with extremely enlarged core diameters of up to 100 µm for laser-based multi-gigabit short-range optical networks. We demonstrate some results of 100 µm core MMF graded index profile optimization performed by a proposed solution, which provides a selected mode staff differential mode delay (DMD) reduction over the “O”-band under particular launching conditions. Earlier on, a developed alternative model for a piecewise regular multimode fiber optic link operating in a few-mode regime for the computation of laser-excited optical pulse dynamics during its propagation over an irregular silica graded-index MMF with an extremely large core diameter, is utilized to estimate the potentiality of fiber optic links with the described MMFs. Here, we also present the comparison results of the simulation of 10GBase-LX optical signal transmission over 100 µm core MMFs with conventional and optimized graded-index refractive index profiles.